The energy spectra of two interacting electrons in a parabolic quantum dot in the presence of a magnetic field: Interpolation approach - AbuSaa, M; ElSaid, M (Royal Swedish Acad Sciences, 1996)
An interpolation formula between the energies of a quantum dot in high- and low-magnetic field limits is proposed. The formula is implemented to produce the energy spectra of the parabolic quantum dot in the presence of a magnetic field of arbitrary strength. The transitions in the angular momenta of the ground state energy of interacting electrons confined in the quantum dot as a function of magnetic field strength is studied. A good agreement is obtained when our results are tested against exact numerical work.
Keywords: 2 Electrons; Dynamic-Response; Excitons; Confinement; Spectroscopy; Helium; Boxes